2015
DOI: 10.1111/mec.13149
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sex‐biased dispersal on opposite‐sexed spatial genetic structure and inbreeding risk

Abstract: Natal sex-biased dispersal has long been thought to reduce the risk of inbreeding by spatially separating opposite-sexed kin. Yet, comprehensive and quantitative evaluations of this hypothesis are lacking. In this study, we quantified the effectiveness of sex-biased dispersal as an inbreeding avoidance strategy by combining spatially explicit simulations and empirical data. We quantified the extent of kin clustering by measuring the degree of spatial autocorrelation among opposite-sexed individuals (FM structu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 72 publications
0
25
0
Order By: Relevance
“…First, spatially clustered kinship generates a risk of potentially deleterious inbreeding (Keller & Waller ; Blyton et al . ). Previous studies on cooperatively breeding birds have shown that dispersal by either both sexes or, more commonly, by females can be an efficient mechanism to avoid inbreeding (Walters et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…First, spatially clustered kinship generates a risk of potentially deleterious inbreeding (Keller & Waller ; Blyton et al . ). Previous studies on cooperatively breeding birds have shown that dispersal by either both sexes or, more commonly, by females can be an efficient mechanism to avoid inbreeding (Walters et al .…”
Section: Discussionmentioning
confidence: 97%
“…Such spatial clustering of relatives also has important consequences in terms of mate choice. First, spatially clustered kinship generates a risk of potentially deleterious inbreeding (Keller & Waller 2002;Blyton et al 2015). Previous studies on cooperatively breeding birds have shown that dispersal by either both sexes or, more commonly, by females can be an efficient mechanism to avoid inbreeding (Walters et al 2004;Blackmore et al 2011;Nelson-Flower et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…extra-group mating52. Extra-group paternity (EGP) is common in mammals, accounting for a mean of 29.2% of offspring in 20 of 26 investigated species53; in rhesus macaques, levels of EGP range from 16–36% (Ruiz-Lambides unpublished data)5354.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of overlapping generations, more realistic of wild populations, extends the genetic signal of sex‐biased dispersal as mothers and daughters cluster geographically, while male offspring disperse farther from their natal area (Blyton et al. ). Juvenile dispersal of fisher from their natal areas usually begins in mid‐late winter (~10 months post‐birth), with the majority of juvenile dispersal occurring from February to September (Lofroth et al.…”
Section: Discussionmentioning
confidence: 99%
“…With nonoverlapping generations, microsatellite markers can detect sex-biased dispersal when individuals are sampled after dispersal, but before reproduction, when alleles from dispersers will be transmitted to its offspring. The presence of overlapping generations, more realistic of wild populations, extends the genetic signal of sex-biased dispersal as mothers and daughters cluster geographically, while male offspring disperse farther from their natal area (Blyton et al 2015). Juvenile dispersal of fisher from their natal areas usually begins in mid-late winter (~10 months post-birth), with the majority of juvenile dispersal occurring from February to September (Lofroth et al 2010, Sweitzer et al 2015.…”
Section: Sex-biased Dispersalmentioning
confidence: 99%